Meaning Construction in Indonesian Language and Literature Education Students' Speaking during Academic Discussions in Higher Education - joko setiyono; Muhammad Sholehhudin; Anik Puspitasari (IKIP PGRI Bojonegoro, 2026)
This study aims to describe the meaning construction and speaking strategies of first-year students of Class 1A of the Indonesian Language and Literature Education Study Program at IKIP PGRI Bojonegoro during academic discussions. This investigation focuses on how students construct meaning explicitly and implicitly, negotiate understanding, and use linguistic and pragmatic strategies in small group interactions. This study adopted a qualitative case study design. Data were obtained through classroom observations, discussion recordings, and transcriptions of spoken discourse, then analyzed using Gee and Halliday's meaning construction theory, Thomas's pragmatics, Fairclough's critical discourse analysis, Mercer's interthinking concept, and Brown and Yule's oral interaction framework. The results show that meaning construction occurs through clarification, negotiation, repair, and the use of adjacent pairs. These findings contribute to the development of speaking skills teaching, particularly in understanding how beginning students construct meaning and participate effectively in academic discussions.